-2.7-2.7=-2.1x-2.1

Simple and best practice solution for -2.7-2.7=-2.1x-2.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2.7-2.7=-2.1x-2.1 equation:


Simplifying
-2.7 + -2.7 = -2.1x + -2.1

Combine like terms: -2.7 + -2.7 = -5.4
-5.4 = -2.1x + -2.1

Reorder the terms:
-5.4 = -2.1 + -2.1x

Solving
-5.4 = -2.1 + -2.1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2.1x' to each side of the equation.
-5.4 + 2.1x = -2.1 + -2.1x + 2.1x

Combine like terms: -2.1x + 2.1x = 0.0
-5.4 + 2.1x = -2.1 + 0.0
-5.4 + 2.1x = -2.1

Add '5.4' to each side of the equation.
-5.4 + 5.4 + 2.1x = -2.1 + 5.4

Combine like terms: -5.4 + 5.4 = 0.0
0.0 + 2.1x = -2.1 + 5.4
2.1x = -2.1 + 5.4

Combine like terms: -2.1 + 5.4 = 3.3
2.1x = 3.3

Divide each side by '2.1'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| (15x/3)=47 | | 4q-(7q+10)=6-(5q-5) | | n-8=21 | | (2X+3)(5X+4)=20 | | 7x-9=-9x-7 | | 2-3(x-7)=1 | | 6(n-6)+7n=-140 | | x^1/3=4/3 | | 8x=-3+1 | | 2000+100h=1800+150h | | 1100+800+4z=700+300+7z | | 0.6x+4.3=3.4 | | 2y=-5y-24 | | (8x^4+3x^3-5)-(2x^2-6x+5)= | | 22-16=x | | 2(x+3)-1=3 | | 7/n=4/8 | | 6(4z-1)-3(z+6)=13(z+1) | | k-1/3=10 | | 4(-6)(-5)-2(-5)(2)= | | 2/5x-12=2 | | 6x+6y+6=0 | | 3*6-12/6 | | x-3/8=1x/3 | | 4x+6=4x-5 | | 6y+18=y+11 | | [[24]/[56]] | | 78=5t-7 | | -7(8x-7)+8(1+5x)=-23 | | 1-2x=3x-11 | | x-3/8=1-x/3 | | 3m+5=25 |

Equations solver categories